Acceleration Cost Analysis with Critical Path Method: (Case Study on Jakarta Sewerage Development Project Zone 1, Package 2: Construction of Wastewater Sewers in Area 1-1) - Hartawan, Ade Sholeh; Witjaksana, Budi; Wulandari, Esti (CV. Proaksara Global Transeduka, 2024)
In a construction project, preparation work typically includes tasks related to setting up work facilities, conducting field investigations, obtaining permits, and non-structural activities. The Jakarta Sewerage Development Project Zone 1, Package 2, which involves the construction of sewers in Area 1-1, is currently in the preparation phase and is experiencing challenges due to a complex permit process. This has led to minimal progress as the initial project planning did not consider the time needed to secure the necessary permits for implementation. The author is therefore evaluating the project timeline to gauge performance during the preparation phase before actual construction begins. This study utilizes the Critical Path Method (CPM) scheduling technique in Microsoft Project to pinpoint critical activities. Upon analysis, it was found that the budget plan for Package 2 of the Jakarta Sewerage Development Project (Zone 1) was detailed and included various work descriptions, with a total budget of IDR 862,292,086,196. However, delays have occurred, resulting in a 17-day setback in the project schedule, necessitating work acceleration. To bring the project duration back in line with the original schedule as per the contract, acceleration was required. This was carried out on the Shaft Construction C-8.1, which was initially set to take 80 days but was shortened to 63 days through time acceleration, incurring a cost of IDR 23,279,288.